2015
DOI: 10.3897/zookeys.470.8548
|View full text |Cite
|
Sign up to set email alerts
|

Annotated type catalogue of the Megaspiridae, Orthalicidae, and Simpulopsidae (Mollusca, Gastropoda, Orthalicoidea) in the Natural History Museum, London

Abstract: The type status is described for 65 taxa of the Orthalicoidea, classified within the families Megaspiridae (14), Orthalicidae (30), and Simpulopsidae (20); one taxon is considered a nomen inquirendum. Lectotypes are designated for the following taxa: Helix brephoides d’Orbigny, 1835; Simpulopsis cumingi Pfeiffer, 1861; Bulimulus (Protoglyptus) dejectus Fulton, 1907; Bulimus iris Pfeiffer, 1853. The type status of Bulimus salteri Sowerby III, 1890, and Strophocheilus (Eurytus) subirroratus da Costa, 1898 is now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…However, since no specimens have been located in the MNHN collection, it is assumed that all material was returned by Crosse and is now preserved in Madrid. Breure and Ablett (2015 : 39, 45) suggested that this taxon belongs to Clatrorthalicus , and inspection of the MNCN material corroborates this point of view. It may be noted that this species strongly resembles Clathrorthalicus phoebus (Pfeiffer, 1863), and further studies of the variation and distribution of both species are needed to fully assess their taxonomic positions as a synonymy might be involved.…”
Section: Systematicsmentioning
confidence: 63%
See 4 more Smart Citations
“…However, since no specimens have been located in the MNHN collection, it is assumed that all material was returned by Crosse and is now preserved in Madrid. Breure and Ablett (2015 : 39, 45) suggested that this taxon belongs to Clatrorthalicus , and inspection of the MNCN material corroborates this point of view. It may be noted that this species strongly resembles Clathrorthalicus phoebus (Pfeiffer, 1863), and further studies of the variation and distribution of both species are needed to fully assess their taxonomic positions as a synonymy might be involved.…”
Section: Systematicsmentioning
confidence: 63%
“…As Breure and Ablett (2015) remarked, this species may be closely allied to Kara thompsonii (Pfeiffer, 1845) and Kara yanamensis (Morelet, 1863), and upon further studies may prove to be a synonym of either of these species.…”
Section: Systematicsmentioning
confidence: 86%
See 3 more Smart Citations